If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q + -2r = 4 Solving q + -2r = 4 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2r' to each side of the equation. q + -2r + 2r = 4 + 2r Combine like terms: -2r + 2r = 0 q + 0 = 4 + 2r q = 4 + 2r Simplifying q = 4 + 2r
| 27+5n=7(4n-6) | | 15x+8=25x+12 | | 3y-21=18 | | x=ax+3x | | 0.15b-1=-5.5 | | 368=8(-2+6x) | | 3(x+6)=-3(x-2)+18 | | 2.500(15y+10)-2(4y+7)=0 | | X-(-4)=34 | | b=ax+3x | | 4(x+3)=-2(4x-9)+2x | | 85=-3+2(4-5r) | | 7(a-8)=28-5a | | 9+c=-18 | | -34=-45 | | 4(3x+1)=24 | | 1-5b=2-4b | | 2-5p=22 | | 3x-16=-41+8x | | e+(-4)=7 | | 3x^3+10x^2-4x-35=0 | | x^2+3x^2+2x= | | 3n+2n=5 | | X+-4.2=-3 | | x^5-4x^4+x^3-7x+1=0 | | -91=p-6(-p+7) | | -17x-23x=12x-2 | | -17x-23x=12x-2 | | x^2-x-6%x^2-5x+6 | | f(x)=zx^2+12x+14 | | 2(u-8)-1=-5(-5u+4)-5u | | (-15)+e=12 |